2023
DOI: 10.3390/antibiotics12081331
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Activity and Molecular Docking Studies of the Biotransformation of Diterpene Acanthoic Acid Using the Fungus Xylaria sp.

Andrey Moacir do Rosario Marinho,
Claudia Maria S. C. de Oliveira,
João Victor Silva-Silva
et al.

Abstract: Biotransformations are reactions mediated by microorganisms, such as fungi. These bioreactions have high chemo- and stereoselectivity on organic substrates and can be applied in the search for new bioactive compounds. In this study, acanthoic acid (AA) was biotransformed using the fungus Xylaria sp., giving the novel compound 3β,7β-dihydroxyacanthoic acid (S1). Both the AA and the product S1 were tested against Gram-positive and Gram-negative bacteria. To identify and validate possible biological targets as en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…Research has documented the considerable efficacy of an ethanol extract derived from the stems of A. flava against a wide range of bacterial and fungal strains [3]. The ability of secondary metabolites to obstruct critical biological processes, including protein and cell wall synthesis, is the main factor responsible for these activities [4,5]. In addition, studies have demonstrated that berberine, a compound found in A. flava, inhibits these synthesis pathways [6].…”
Section: Introductionmentioning
confidence: 99%
“…Research has documented the considerable efficacy of an ethanol extract derived from the stems of A. flava against a wide range of bacterial and fungal strains [3]. The ability of secondary metabolites to obstruct critical biological processes, including protein and cell wall synthesis, is the main factor responsible for these activities [4,5]. In addition, studies have demonstrated that berberine, a compound found in A. flava, inhibits these synthesis pathways [6].…”
Section: Introductionmentioning
confidence: 99%